A Next-generation Exoplanet Atmospheric Retrieval Framework for Transmission Spectroscopy (NEXOTRANS): Comparative Characterization for WASP-39 b Using JWST NIRISS, NIRSpec PRISM, and MIRI Observations - Tonmoy Deka; Tasneem Basra Khan; Swastik Dewan; Priyankush Ghosh; Debayan Das; Liton Majumdar (The Astrophysical Journal, 2025)
The advent of JWST has marked a new era in exoplanetary atmospheric studies, offering higher-resolution data and greater precision across a broader spectral range than previous space-based telescopes. Accurate analysis of these data sets requires advanced retrieval frameworks capable of navigating complex parameter spaces. We present NEXOTRANS , an atmospheric retrieval framework that integrates Bayesian inference using UltraNest / PyMultiNest with four machine learning algorithms: Random Forest , Gradient Boosting , K-Nearest Neighbor , and Stacking Regressor . This hybrid approach enables a comparison between traditional Bayesian methods and computationally efficient machine learning techniques. Additionally, NEXOTRANS incorporates NEXOCHEM , a module for solving equilibrium chemistry. We applied NEXOTRANS to JWST observations of the Saturn-mass exoplanet WASP-39 b, spanning wavelengths from 0.6 to 12.0 μ m using NIRISS, NIRSpec PRISM, and MIRI. Four chemistry models—free, equilibrium, modified hybrid equilibrium, and modified equilibrium-offset chemistry—were explored to retrieve precise volume mixing ratios (VMRs) for H _2 O, CO _2 , CO, H _2 S, and SO _2 . Absorption features in both NIRSpec PRISM and MIRI data constrained SO _2 log VMRs to values between −6.25 and −5.73 for all models except equilibrium chemistry. High-altitude aerosols, including ZnS and MgSiO _3 , were inferred, with constraints on their VMRs, particle sizes, and terminator coverage fractions, providing insights into cloud composition. For the best-fit modified hybrid equilibrium model, we derived supersolar elemental abundances of $\,\rm{O/H}\,=14.{12}_{-1.82}^{+2.86}× $ solar, $\,\rm{C/H}\,=21.{37}_{-3.18}^{+4.93}× $ solar, and $\,\rm{S/H}\,=5.{37}_{-0.65}^{+0.79}× $ solar, along with a C/O ratio of ${1.35}_{-0.02}^{+0.05}× $ solar. These results demonstrate NEXOTRANS ’s potential to enhance JWST data interpretation, advancing comparative exoplanetology efficiently.